2021
DOI: 10.1101/2021.05.07.443132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A bioorthogonal chemical reporter for fatty acid synthase-dependent protein acylation

Abstract: Cells acquire fatty acids from dietary sources or via de novo palmitate production by fatty acid synthase (FASN). Although most cells express FASN at low levels, it is upregulated in cancers and during replication of many viruses. The precise role of FASN in disease pathogenesis is poorly understood, and whether de novo fatty acid synthesis contributes to host or viral protein acylation has been traditionally difficult to study. We describe a cell permeable, click-chemistry compatible alkynyl-acetate analog (A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…6C), suggests that the FASN is also critical to generating the CoA species used for these reactions. In support of this notion, two recent studies have found that FASN generates an array of fatty acyl chains than just 16:0 and that FASN supports the generation of myristoyl-CoA and stearoyl-CoA and their subsequent attachment to proteins (61,62). Does the loss of ZDHHC5 and FASN activity impact the SARS-CoV2 infection cycle by other mechanisms?…”
Section: Discussionmentioning
confidence: 94%
“…6C), suggests that the FASN is also critical to generating the CoA species used for these reactions. In support of this notion, two recent studies have found that FASN generates an array of fatty acyl chains than just 16:0 and that FASN supports the generation of myristoyl-CoA and stearoyl-CoA and their subsequent attachment to proteins (61,62). Does the loss of ZDHHC5 and FASN activity impact the SARS-CoV2 infection cycle by other mechanisms?…”
Section: Discussionmentioning
confidence: 94%
“…5 D), suggests that the FASN is also critical to generating the CoA species used for these reactions. In support of this notion, two recent studies have found that FASN generates an array of fatty acyl chains beyond just 16:0 and that FASN supports the generation of myristoyl-CoA and stearoyl-CoA and their subsequent attachment to proteins ( 68 , 69 ).…”
Section: Discussionmentioning
confidence: 88%